Effect of fresh and fermented camel milk and colostrums on body weight and blood glucose level in alloxan-induced diabetic rabbits - Sahar A Elhassan; Awad M Babeker; Mohammed Alhadi Ebahiem; Sallam A Bakhiet (International Journal of Veterinary Science and Research - Peertechz Publications, 2022)
To study the effect of fresh camel milk, fermented camel milk and colostrums on blood glucose levels 30 Alloxan-induced diabetic rabbits were taken. Diabetes was induced in rabbits using Alloxan, the diabetic rabbits were then treated with fresh camel milk, fermented camel milk and colostrums as well as insulin for 60 days. The results demonstrated that the body weight of rabbits treated with camel milk and its derivatives found to be kept within the accepted body weights range of 1.8- 2.5 kg. The lowest serum glucose levels were recorded by Group 1 (control), Group 3 (diabetic-treated with colostrums), Group 4 (diabetic-treated with milk), Group 5 (diabetic-treated with gars) and Group 6 (diabetic-treated with Insulin16 mg/kg body weight daily for 8 weeks) and the levels found to be within the normal level range of 75- 140 mg/dl, the highest level of serum glucose level was recorded by Group 2 (diabetic-non supplemented) and it was higher than the upper limit of the normal range.